Analysis of the High-Speed Impact Effect of Raindrops on Prestressed Wind Turbine Blades and the Equivalent Load Construction Method - Xiufeng Xu; Yichao Xu; Aiguo Zhou; Zhengzhao Lai (预应力技术)
The finite element method and smoothed particle hydrodynamics (SPH) method are used to simulate the high-speed impact of a single raindrop on a prestressed wind turbine blade, and the factors affecting impact pressure and stress in a single raindrop impact, such as impact speed and raindrop diameter, are analyzed. In addition, the coupling generated by the simultaneous high-speed impact of dual raindrops is analyzed, and the effect of the distance between raindrop centers is analyzed. To address the difficulty in calculation due to the large number of impacting raindrops during the rainfall process, based on the calculation results of single raindrop impacts, the method of applying equivalent loads of raindrop impacts is proposed and validated by the stress distribution and the stress at each time point, thus ensuring the simulation accuracy of using the equivalent load of raindrop impact for the actual raindrop impact.